Людинозамінні технології як напрямок підвищення продуктивності праці в гірничо-металургійному комплексі - Середа, Г.В. (Економічний вісник Донбасу, 2026)
У статті досліджено вплив людинозамінних технологій на продуктивність праці в гірничо‑металургійному комплексі України в умовах дефіциту робочої сили та структурних змін ринку праці. Проаналізовано механізацію, автоматизацію, роботизацію, цифровізацію та AI‑аугментацію, а також їхній прямий та опосередкований ефект через зростання сукупної факторної продуктивності. Показано необхідність інвестицій у людський капітал та врахування соціально‑ергономічних аспектів при впровадженні технологій. The article examines the impact of human‑replacing technologies on labour productivity in Ukraine’s mining and metallurgical sector under conditions of workforce shortages and large‑scale structural changes in the labour market caused by war and demographic decline. The study analyses the effects of mechanization, automation, robotization, digitalization and AI‑augmentation, highlighting both their direct contribution to productivity growth and their indirect impact through increased total factor productivity. Empirical evidence from international and industry‑specific studies demonstrates that higher robot density is associated with productivity gains, particularly in low‑robotized sectors such as Ukraine’s mining and metallurgical industry. The research emphasizes that the implementation of human‑replacing technologies leads to significant transformations in skill demand, reducing reliance on low‑skilled labour while increasing the need for qualified engineers, system operators and specialists in digital technologies. Successful technological modernization requires continuous investment in human capital, reskilling and the development of digital and engineering competencies. The article also stresses the importance of integrating ergonomic assessments and human‑systems‑interaction approaches into automation projects to prevent cognitive overload, occupational stress and operational risks for control‑room operators. These findings underscore the strategic role of human‑replacing technologies in enhancing industrial productivity and ensuring the long‑term resilience of Ukraine’s mining and metallurgical sector.